2021
DOI: 10.3390/s21072541
|View full text |Cite
|
Sign up to set email alerts
|

Match Analysis of Soccer Refereeing Using Spatiotemporal Data: A Case Study

Abstract: This case study explored how spatiotemporal data can develop key metrics to evaluate and understand elite soccer referees’ performance during one elite soccer match. The dynamic position of players from both teams, the ball and three elite referees allowed to capture the following performance metrics: (i) assistant referees: alignment with the second last defender; (ii) referee: referee diagonal movement—a position density was computed and a principal component analysis was carried to identify the directions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The slopes of the PCA and LR LvsW directional ellipses provide information about the main direction of player displacement in the full range of the twodimensional field space, which describes the player's directional behavior in a contextualized way. This approach was recently used by Gonc xalves et al 21 to assess a referee's performance between the first and second halves of an elite adult international match by means of a PCA ellipse, but to the best of the authors' knowledge, this is the first time that it is applied to outfield players. Figure 1 shows how a representative outfield player's directionality is determined by PCA and LR LvsW models at SSG60 and SSG50 (that is, when the length/width ratio is greater than 1), while the LR WvsL model fails to describe it accurately.…”
Section: Discussionmentioning
confidence: 99%
“…The slopes of the PCA and LR LvsW directional ellipses provide information about the main direction of player displacement in the full range of the twodimensional field space, which describes the player's directional behavior in a contextualized way. This approach was recently used by Gonc xalves et al 21 to assess a referee's performance between the first and second halves of an elite adult international match by means of a PCA ellipse, but to the best of the authors' knowledge, this is the first time that it is applied to outfield players. Figure 1 shows how a representative outfield player's directionality is determined by PCA and LR LvsW models at SSG60 and SSG50 (that is, when the length/width ratio is greater than 1), while the LR WvsL model fails to describe it accurately.…”
Section: Discussionmentioning
confidence: 99%
“… Hossner et al (2019) revealed that the referees’ decision-making had been affected by the decision-making position during the FIFA World Cup 2014. Gonçalves et al (2021) found that the referees maintained a distance of 0–18 m to the ball location in the observed European leagues such as the English Premier League, German Bundesliga, and the Spanish La Liga. Oliveira et al (2011) found that no significant association was found between the Brazilian referee’s distance from a foul play and the accuracy of the decision-making.…”
Section: Introductionmentioning
confidence: 97%
“…Another potential reason is related to the referees’ physical preparedness. In order to observe the on-going behaviors of players and execute the rules of a match from a relatively suitable distance and angle, referees must keep appropriate distance to the players and ball and also move quickly and constantly from one area of the football field to another ( Ghasemi et al, 2009 ; Castagna et al, 2013 ; Gonçalves et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, referees wear GPS devices that track their movement throughout the match. 11,12 For example, Gonc xalves et al 11 explored how spatiotemporal data can develop key metrics to evaluate and understand elite soccer referees' performance during one elite soccer match. The key metrics were obtained by principal component analysis and crucially, the analysis provided a starting point to elaborate normative behavior models from the referee's movement performance.…”
Section: Introductionmentioning
confidence: 99%